2019
DOI: 10.1177/2309499019832808
|View full text |Cite
|
Sign up to set email alerts
|

Pain, function, and patient satisfaction after arthroscopic treatment of elbow in a retrospective series with minimum of 5-year follow-up

Abstract: Background: The clinical indications for elbow arthroscopic procedures have expanded through last decades. The aim of the study was to assess the functional results and patient satisfaction after arthroscopic treatment of various elbow conditions after a minimum 5-year follow-up. Methods: We conducted a retrospective study of a consecutive patient cohort who had undergone unilateral elbow arthroscopy between 2008 and 2010. The main outcomes were Disabilities of the Arm, Shoulder and Hand (DASH) score and a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…44 We were unable to identify any randomised controlled trials of the efficacy of elbow arthroscopy. Publications describe clinical outcomes of patient cohorts--such as the series of elbow arthroscopic debridement surgery performed on patients with primary or post-traumatic osteoarthritis, 51 and osteochondritis dissecans and posterior impingement. [52][53][54][55] Only case reports and expert opinions on several elbow pathologies suggest the use of arthroscopic procedures in evaluation and treatment.…”
Section: Why Are There Secular Trends In Shoulder Arthroscopy?mentioning
confidence: 99%
“…44 We were unable to identify any randomised controlled trials of the efficacy of elbow arthroscopy. Publications describe clinical outcomes of patient cohorts--such as the series of elbow arthroscopic debridement surgery performed on patients with primary or post-traumatic osteoarthritis, 51 and osteochondritis dissecans and posterior impingement. [52][53][54][55] Only case reports and expert opinions on several elbow pathologies suggest the use of arthroscopic procedures in evaluation and treatment.…”
Section: Why Are There Secular Trends In Shoulder Arthroscopy?mentioning
confidence: 99%
“…It has been suggested that any functional restoration or symptom relief that can be achieved by open surgery can be fully accomplished by arthroscopy. 34,45,46 A recent study also reported the comparable clinical outcomes associated with arthroscopic OCA with the important finding that neither procedure can guarantee excellent outcomes in patients with advanced osteoarthritis. 47 In a systematic review, Kim et al reported that both open and arthroscopic OCA improve ROM and clinical scores and that open debridement is associated with a relatively higher complication and reoperation rates than arthroscopic OCA.…”
Section: Postoperative Managementmentioning
confidence: 83%
“…1,2 Complication rates should be minimalized to avoid reoperations because this significantly impacts patientreported outcome measures. 3 As the use of arthroscopy increases for treating elbow pathology, insight into the incidence and type of complications should help surgeons refine their surgical techniques to reduce the complication rates further. Complications associated with elbow arthroscopy are wound infections, transient or permanent nerve palsies, hematomas, heterotopic ossifications, stiffness, and chronic pain; with some requiring additional surgical intervention.…”
mentioning
confidence: 99%